Inhibition of Antibacterial Bioactive Compounds from Awar-Awar (Ficus septica Burm, F.) Leaves for Methicillin Resistant Staphylococcus aureus (MRSA) Infection: an In Silico Study - Friska Amanda Nurlailiyah; Ni Putu Alira Kinanti Febrina Putri; Siti Saidah Qurrotul A’yun; Sofia Nur Cahyani; Aneila Maritza Larasati; Victor Alvianoes Guterez Hose; Fatchiyah Fatchiyah (JSMARTech, 2023)
Methicillin resistant Staphylococcus aureus (MRSA) is a type of Staphylococcus aureus infection that can increase the patients’ number with prevalence variation in each country. Methicillin resistant Staphylococcus aureus (MRSA) can be treated by inhibiting the activity of the BlaR1 transducer protein as an MRSA sensor against transmembrane antibiotics using bioactive compounds. Ficus septica is a local variety that has potential as an antibacterial. In silico study of the bioactive compounds found in Ficus septica can inhibit the synthesis of Staphylococcus aureus cell wall based on molecular docking tests with the control compound is Linezolid as antibiotics. In addition, ADME prediction, binding affinity, and binding site analysis were also performed. The results showed that there were 9 active compounds from Ficus septica leaves which had antibacterial potential and fulfilled Lipinski's rules criteria. Analysis of the binding site indicated that Coumarin compound could bind to the most BlaR1 protein active sites than other bioactive compounds in Ficus septica, including on the Lys526 and Thr527 active sites. Based on interaction analysis, it can be concluded that the Coumarin compounds of Ficus septica leaves can provide a therapeutic effect that can fight MRSA infection which can be proven by in vitro tests.